Effect of Examination on Instructional Practices of Elementary School Teachers:A Mixed Methods Study - Sajid Masood, Abdul Hameed, (PJE, 2023)
Examinations conducted by the Punjab Examination Commission (PEC) at grade VIII are important as intended and unintended consequences are associated with examination results influence the teaching and learning processes in schools. A mixed methods sequential explanatory study was conducted to investigate the effects of the examinations conducted by the PEC on instructional practices of teachers at the elementary level in seven districts of the Punjab. In the quantitative phase survey data was collected from 521 elementary school teachers teaching in seven districts of the Punjab selected through multistage random sampling. The quantitative results were used to select participants for the study’s qualitative phase through a maximum variation strategy of purposive sampling. The quantitative phase indicated that female teachers perceived more effects of examinations on their instructional practices. Moreover, teachers belonging to age group 42-48 experienced most of the effects of examination on their instructional practices as compared to teachers belonging to other age groups. Similarly, teachers belonging to district 3 (Okara) experienced more effects of the examination on their instructional practices as compared to teachers serving in other districts. The qualitative data indicated that instruction was driven by the examination. Teacher-centred instructional strategies were dominant. Paper patterns defined the instruction and tests were extensively practiced in class. Teachers used strategies for helping students to attempt MCQs. One of the objectives of the PEC was to improve teaching and learning and in light of the present study it remains hard to achieve. The findings of the study pose several challenges for the examination board, curriculum and educational authorities in the Punjab.